Knife Edge Test of Mechanical Desiccated Coconut - Stephanus K.; Lukman Adlin Harahap; Adian Rindang (Jurnal Rekayasa Pangan dan Pertanian, 2015)
This research was done to test the effect of knife edge on the effective capacity of the equipment, percentage of material that was grated uncompletely, percentage of material left in the equipment, and yield. This research was using non factorial completely randomized design. It was found that the effective capacity of the equipment, percentage of material that was grated completely, percentage of material left in the equipment, and yield on two knifes edge/cm2 are 44,821, 5,87%, 11,69%, and 88,31% kg/hr respectively. On three knifes edge/cm2 are 46,049, 3,97%, 9,68%, and 90,32% kg/hr respectively. On four knifes edge/cm2 are 48,988, 3,79%, 6,74%, and 93,26% kg/hr respectively. The results showed that number of knife edge had significant effect on the percentage of material that was grated uncompletely, percentage of material left in the equipment, and yield and had no effect on the effective capacity. The main cost from year one to year seven were Rp. 35,29, Rp. 32,92, Rp. 32,13, Rp. 31,73, Rp. 31,49, Rp. 31,37, and Rp. 31,23 per kg respectively. Break even point from year one to year seven were 2897,76, 1558,97, 1113,32, 890,89, 757,71, 687,64, 606,13 kg respectively. The result of net present value from 6% of bank rate was Rp. 838.406.384,79 which means this business was competent. The internal rate of return was 35,56% which means this business was competent if the bank rate were not more than 35,56%. Keywords : Knife edge, grater, desiccated coconut